2015
DOI: 10.1016/j.cden.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Should Antibiotics Be Prescribed to Treat Chronic Periodontitis?

Abstract: Synopsis While scaling and root planing is a cost-effective approach for initial treatment of chronic periodontitis, it fails to eliminate subgingival pathogens and halt progressive attachment loss in some patients. For some patients, adjunctive use of systemic antibiotics immediately after completion of scaling and root planing can enhance the degree of clinical attachment gain and probing depth reduction provided by nonsurgical periodontal treatment. This article discusses the rationale for prescribing adjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…Current periodontitis treatment involves surgical‐ and non‐surgical mechanical therapies, which are usually effective in relieving local inflammation. Systemic or local administration of antibiotics may be used to treat severe and refractory manifestations of the disease . These treatment strategies are often only temporarily effective and recurrence of the disease is common, possibly due to the re‐emergence of pathogens such as P gingivalis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current periodontitis treatment involves surgical‐ and non‐surgical mechanical therapies, which are usually effective in relieving local inflammation. Systemic or local administration of antibiotics may be used to treat severe and refractory manifestations of the disease . These treatment strategies are often only temporarily effective and recurrence of the disease is common, possibly due to the re‐emergence of pathogens such as P gingivalis .…”
Section: Discussionmentioning
confidence: 99%
“…Systemic or local administration of antibiotics may be used to treat severe and refractory manifestations of the disease. [46][47][48] These treatment strategies are often only temporarily effective and recurrence of the disease is common, 49,50 possibly due to the re-emergence of pathogens such as P gingivalis. 51 Our previous work demonstrated that SAPP represses expression of gingipains and fimbrial proteins in P gingivalis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…; Teeuw et al. ; Walters and Lai ). P. gingivalis, a predominant causative factor of periodontitis, has been reported to accelerate atherosclerosis in animal models (Hayashi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are indicated for treating odontogenic infections, oral nonodontogenic infections, as prophylaxis against focal and local infection, and the spread of infection . The most common oral infections are pulpitis and periapical periodontitis, for which antibiotics are not required . However, studies have shown that antibiotics are often prescribed for these conditions .…”
Section: Introductionmentioning
confidence: 99%
“…3 The most common oral infections are pulpitis and periapical periodontitis, for which antibiotics are not required. 4,5 However, studies have shown that antibiotics are often prescribed for these conditions. 5,6 The awareness of dentists regarding the rational use of antibiotics and their antibiotic prescribing behaviors are important.…”
Section: Introductionmentioning
confidence: 99%